Impact of a multi-strain probiotic administration on peri-rectal colonization with drug-resistant Gram-negative bacteria in preterm neonates - Sowden, Marwyn; van Niekerk, Evette; Bulabula, Andre Nyandwe Hamama; Dramowski, Angela; Whitelaw, Andrew; Twisk, Jos; van Weissenbruch, Mirjam Maria (Frontiers in Pediatrics, 2022)
Background: Infections caused by drug resistant Gram-negative bacteria (DR-GNB) are a major health concern for hospitalized preterm neonates, globally. The aim of this study was to investigate the effect of a multi-strain probiotic on the incidence of rectal colonization with DR-GNB in preterm neonates. Methods: A double-blind, placebo-controlled, randomized clinical trial was conducted including 200 neonates, randomly allocated to a multi-strain probiotic (n=100) or placebo (n=100). Results: Fifteen percent of the neonates showed perirectal colonization with DR-GNB on the day of enrolment indicating probable maternal-to-neonate (vertical) bacterial transmission or environmental acquisition at time of delivery, with no difference between groups. Acquisition of further DR-GNB colonization was rapid, with an increase from 15% on the day enrolment to 77% by day 7 and 83% by day 14 of life. By day 7 (corresponding to early gut colonization), neonates in the probiotic group were 57% less likely to have perirectal DR-GNB colonization (OR: 0.43 (0.20 to 0.95); p=0.04) and by day 14 (corresponding to late gut colonization), neonates in the probiotic group were 93% less likely to have perirectal DR-GNB colonization (OR: 0.07 (0.02 to 0.23); p<0.001). Conclusion: Hospitalized neonates showed substantial perirectal colonization with DR-GNB at enrolment and further rapid acquisition of DR-GNB in the first 2 weeks of life. The use of a multi-strain probiotic was effective in reducing early and late neonatal gut colonization with DR-GNB.